The upper Tanana Dene: people of this land - Simeone, William E., author; University of Alaska Press, publisher (Colorado State University. Libraries, 2023)
This volume conveys the history and knowledge of Dene elders. Oral accounts reveal a unique perspective and offer commentary on continuity and change over the past hundred years. These narratives, along with photographs and illustrations, show the history of the region alongside a portrait of the people themselves.--Provided by publisher.
Living from the Land -- Life on the Land: The Seasonal round 1910-1940 -- Udzih (UT & T) and Diniign (Ut), Dendîig (T) Caribou and Moose -- Fishing -- Descent, Marriage and Training of Young People -- Xaxkeh/Xaskee: Rich Men -- Potlatch -- The Fur Trade -- Upper Tanana Dene and the Episcopal Church -- Nondlêed/Noodlee "Those Who Come and Go" (the Americans).
Keywords: Tanana Indians -- Alaska -- Tanana River Valley -- Social life and customs; Tanana Indians -- Social life and customs; Tanana Indians -- Alaska -- Tanacross Region -- Interviews; Indian elders (Indigenous leaders) -- Alaska -- Tanacross Region -- Interviews; Tanana River Valley (Alaska) -- Social life and customs; Tanana River Valley (Alaska) -- History; Tanana Indians -- History